JUDICIAL PRACTICES IN ENFORCING POST-DIVORCE MAINTENANCE RIGHTS FOR WOMEN AND CHILDREN IN INDONESIA - Ahsanul Fahmi; Muhammad Nasir; Nur Anshari; Aminah Aminah; Mohammad Nurunnabi (Indonesia Private Law Review, 2025)
Although CEDAW, the CRC, Indonesian law, and Supreme Court regulations provide a normative basis for protecting women’s and children’s rights after divorce, implementation in practice remains challenging. This paper examines how Religious Courts ensure the fulfillment of these rights, offering the first systematic analysis of post-divorce alimony enforcement as an expression of the courts’ regelende functie. Using a normative method with statutory and conceptual approaches, the study shows that while few divorce rulings explicitly include alimony provisions, the Supreme Court has strengthened judicial authority through several SEMA aimed at protecting vulnerable parties. These reforms are reflected in innovative practices in Surabaya, Gresik, Bengkulu, and Bontang, where institutional collaboration, salary deductions, and digital monitoring systems have improved the effectiveness and certainty of alimony enforcement.